Hens can ingest extruded polystyrene in rearing buildings and lay eggs contaminated with hexabromocyclododecane. (November 2017) - Jondreville, Catherine; Cariou, Ronan; Travel, Angélique; Belhomme, Louis-Jean; Dervilly-Pinel, Gaud; Le Bizec, Bruno; Huneau-Salaün, Adeline; Le Bouquin-Leneveu, Sophie
Abstract: The overall concentration of hexabromocyclododecane (HBCDD) in eggs is low although abnormally high concentrations exceeding 3000 ng g −1 lw have been reported. In order to test whether these contaminations may originate from the ingestion of insulating materials in rearing buildings, a group of 55 hens raised in a collective cage was provided with a 64-g piece of extruded polystyrene (XPS, 2.59% HBCDD of which 75, 15 and 10% as α-, β- and γ-HBCDD, respectively). Hens entirely consumed the piece within 3 days, leading to a mean daily exposure of 4.7 mg HBCDD per kg body weight. Whole egg HBCDD concentration reached a maximum of 1037 ng HBCDD g −1 fresh weight (fw), recorded 2 days after the piece had disappeared, and decreased down to 86 ng g −1 fw within the 19 following days. In all these samples, HBCDD was made of 98.7 ± 0.7 and 1.3 ± 0.6% α- and β-HBCDD, respectively, and 0.1% γ-HBCDD when quantified; it was enriched in (−)α- and (+)β-HBCDD with enantiomeric fractions of 0.438 ± 0.009 and 0.579 ± 0.030, respectively. HBCDD was quantified in all the individual eggs collected the last day of experiment at concentrations ranging between 0.47 and 1361 ng g −1 fw, according to a lognormal distribution. The ingestion of XPS in degraded rearing buildings is thus a plausible cause of on-farm egg contamination by HBCDD which should be strictly avoided. Graphical abstract: Highlights: A group of 55 hens ingested a 64-g piece of extruded polystyrene within 3 days. Composite samples of eggs contained up to 1037 ng HBCDD g −1 fw, mainly as α-HBCDD. Egg HBCDD concentration was highly variable between hens. Eggs were selectively enriched in (−)α- and (+)β-HBCDD.